ChemInform Abstract: A Neutral, Chiral, Bis(imidazolidine)‐Derived NCN‐Type Palladium Pincer Complex with Catalytic Activity. Issue 24 (23rd May 2013) - Arai, Takayoshi; Oka, Ikiyo; Morihata, Takuma; Awata, Atsuko; Masu, Hyuma
Abstract The well‐organized asymmetric reaction sphere of the title complexes is employed to catalyze the asymmetric reaction of nitroalkenes with malononitrile.